Early Breastfeeding Initiation Among Indonesian Women Aged 15–49: Evidence from the 2023 Health Survey - Ari Andayani; Ari Yuniastuti; Intan Zainafree; Dina Nur Anggraini Ningrum (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2026)
Early Breastfeeding Initiation (EBI) achievement globally has only reached 48%, with the target is 70% by 2030. Thus, there is still a 22% gap from the expected target. Although national coverage targets have been achieved in Indonesia, there are still some disparities in maternal characteristics, socioeconomic conditions, and access to maternal health services suggest the presence of underlying determinants that have not been fully explored at the national level. This study aimed to identify factors associated with the practice of EIBF among women of reproductive age in Indonesia. This study uses secondary data of individuals and toddlers SKI 2023 obtained from the Data Center of the Ministry of Health of the Republic of Indonesia, using 14,030 respondents’ data, who were selected based on the completeness of the data and did not have damaged data on the research variables. Chi-Square test was used with a significance level of α = 0.05 and a 95% confidence interval (CI 95%), while multivariate analysis was carried out using the Backward Likelihood Ratio (Backward LR) logistic regression test. The results of the study showed that the type of residential area (PR = 1.044; 95% CI = 1.013-1.077), maternal education level (PR = 0.920; 95% CI = 0.892-0.948), economic status (PR = 0.935; 95% CI = 0.906-0.964), parity (PR = 1.068; 95% CI = 1.024-1.114), ANC frequency (PR=0.958; 95% CI= 0.929-0.989), delivery method (PR=1.597; 95% CI= 1.597-1.745), place of delivery (OR= 1.167; 95% CI=1.021-1.335), and birth weight (PR= 1.265; 95% CI= 1.188-1.348) were associated with EBI practices in WUS in Indonesia. While maternal employment status was not associated with EBI practices in WUS in Indonesia. The variables of place of delivery and birth weight were proven to be confounded by the parity variable. The Indonesian Ministry of Health’s Data Center is advised to add data related to the mother’s age at birth. Women of childbearing age are advised to give birth in health facilities because they have a greater opportunity to practice EBI.